The Great Rock Discography - Strong, Martin C.; Illustrations by Horse, Harry (Edinburgh Canongate, 1998)
A discography of almost 1000 pages and 1000 artists, listing singles, albums, recommendations, chart positions, catalogue numbers, band histories and illustrations up to the end of 1997. This tome is aimed at anyone interested in popular music.
Include Sketches.
Keywords: Rock music -- Rock musicians